An exploratory study of the mechanochemical synthesis of layered double hydroxides - Labuschagne, F.J.W.J. (Frederick Johannes Willem Jacobus) (University of Pretoria, 2021)
Dissertation (MEng (Chemical Engineering))--University of Pretoria, 2020.